Performance analysis of JXTA/JXME applications in hybrid fixed/mobile environments - Piedrahita, Tomás; Montoya, Edwin (Revista Colombiana de Computación, 2006)
P2P applications and mobile computing have merged. Mobile devices are now powerful enough to efectively manage important amounts of information that may be of interest to others. Meanwhile, P2P systems have demonstrated their efectiveness in sharing information. One of the leading technologies that have resulted is JXME, the mobile version of Sun Microsystem’s JXTA. Although some JXTA benchmark analysis have been performed, these tests on JXME have yet to be realized. Keywords: JXTA, JXME, Benchmark, P2P, Mobile Applications.